‘I’m going to look for you and take your kids’: Reproductive justice in the context of immigration enforcement - Fleming, Paul J.; Lopez, William D.; Ledon, Charo; Llanes, Mikel; Waller, Adreanne; Harner, Melanie; Martinez, Ramiro; Kruger, Daniel J. (PloS one, 2019)
Prior research has shown that immigration law enforcement contributes to poor health outcomes-including reproductive health outcomes-among Latinos. Yet no prior research has examined how immigration enforcement might inhibit reproductive justice and limit individual's reproductive autonomy. We utilized data from an existing study that consisted of a partnership with a Latino community in Michigan in which an immigration raid resulted in multiple arrests and deportations midway through data collection. Using cross-sectional survey data (n = 192) where no one was re-interviewed, we used ordinal logistic regression to compare desired pregnancy timing of individuals surveyed prior to and after the raid to determine the impact of an immigration raid on desired timing of next pregnancy. We then used qualitative data-including 21 in-depth interviews and participant observation-collected in the community after the raid to contextualize our findings. Controlling for socio-demographic characteristics, we found that Latinos surveyed in the aftermath of the raid were more likely to report a greater desire to delay childbearing than Latinos surveyed before the raid occurred. Our qualitative data showed that an immigration raid has financial and psychological effects on immigrant families and that a raid may impact reproductive autonomy because people are fearful of these impacts. These finding suggest that current immigration enforcement efforts may influence reproductive decision-making, impede Latinos reproductive autonomy, and that family-friendly immigration policy reform is needed.